KINETIC STUDY OF OIL PALM EMPTY FRUIT BUNCH ENZYMATIC HYDROLYSIS - Diah Meilany; Efri Mardawati; Made Tri Ari Penia Kresnowati; Tjandra Setiadi (Dept. of Chemical Engineering, Diponegoro University, 2017)
As lignocellulosic biomass, Oil Palm Empty Fruit Bunch (OPEFB) can be used as the source of xylose that can be further utilized as the raw material for xylitol production. The processing of OPEFB to xylose comprises of pretreatment and hydrolysis that can be performed enzymatically. This process offers the advantages of moderate operation conditions and more environmentally friendly. This article describes the kinetic study of enzymatic hydrolysis process of OPEFB for producing xylose using self-prepared and commercial xylanase enzymes. Despite the possible mass transfer limitation, the Michaelis Menten kinetics was hypothesized. The results indicated that the reaction at pH 5 and 60°C followed the Michaelis Menten kinetics, with Vm of 0.84 g/L-h and Km of 48.5 g/L for the commercial enzyme, and Vm of 0,38 g/L-h and Km of 0,37 g/L for the self-prepared enzyme. The reaction is affected by temperature, with Ea of 8.6 kcal/gmol. The performance of self-prepared xylanase enzyme was not yet as good as the commercial enzyme, Cellic Htec 2. Keywords: enzymatic hydrolysis; kinetics parameter; OPEFB; xylanase; xylose